Biostratigraphic and Geological Significance of Planktonic Foraminifera, Updated Second Edition - K. BouDagher-Fadel, Marcelle (UCL Press, 2015)
The role of fossil planktonic foraminifera as markers for biostratigraphical zonation and correlation underpins most drilling of marine sedimentary sequences and is key to hydrocarbon exploration. Biostratigraphic and Geological Significance of Planktonic Foraminifera unifies existing biostratigraphic schemes and provides an improved correlation reflecting regional biogeographies. It presents a comprehensive analysis of existing data on fossil planktonic foraminifera genera and their phylogenetic evolution in time and space. Coverage includes presentation and discussion of rarely studied thin sections of planktonic foraminifera, allowing for new developments in dating planktonic foraminifera in carbonates and expanding their usefulness in hydrocarbon exploration.